The extended case method and new social movements: a case of the Tyranny Response Team - Mahoney, Shannon Patrick, author; Swanson, Louis E., advisor; MacDonald, Bradley J., committee member; Raynolds, Laura T., committee member; Taylor, Pete L., committee member (Colorado State University. Libraries, 2006)
Democracy has long held sway in New Social Movement theory as the path to radical politics. This research challenges that presumption by exposing the limitations of democracy, so prevalent in progressive social movements, as an organizing feature of right-leaning, or conservative, movements. Using New Social Movement theory, ethnographic research was done on the Tyranny Response Team, a Second Amendment rights organization along the front range of the Colorado Rockies. The Tyranny Response Team is part of the larger Patriot/Militia Movement that emerged in the mid 1990s. Employing Michael Burawoy's Extended Case Method, a series of anomalies grew out of the fieldwork. These challenged the assumption by New Social Movement theory that the Tyranny Response Team could simply be associated with the robust tradition of radical democracy. Instead, members of the Tyranny Response Team insisted, as did the larger discourse within the Patriot/Militia Movement, that theirs was a movement predicated upon republican, not democratic, principles. Vital to their claim was the critical conviction in the people's right to keep and bear arms. Inquiry into the tradition of republicanism unearthed a narrative that provided a stronger historical, ideological, and theoretical justification for civil activism, than did democracy. Due to the emphasis placed on fundamental rights within the republican tradition, republicanism offers a better understanding for the importance of resistance, autonomy, and self-management in civil society, all critical concerns amongst New Social Movement writers. Through the introduction of three concepts: Inalienable Anarchy, Republican Radicalism and Anti-Federalist Populism, New Social Movement theory is reformulated and extended to integrate political-right movements. Each concept facilitates a move within New Social Movement theory in the direction of incorporating both republicanism and the study of politically-right movements. This extension, while acknowledging a discourse of fundamental rights, ultimately theorizes these rights as essentialist and anchored in religious justification. The appropriation of fundamental rights by the Tyranny Response Team provides them with a God-given arsenal of weapons for their defense of the republic. Moreover, this religious essentialism, within political-right movements as a whole, helps explain their dramatic success over the past twenty-five years.
Keywords: social research; political science; social structure